THE INFLUENCE OF RUSSIAN AND ENGLISH ON THE LEXICAL DEVELOPMENT OF THE KARAKALPAK LANGUAGE: THE INFLUENCE OF RUSSIAN AND ENGLISH ON THE LEXICAL DEVELOPMENT OF THE KARAKALPAK LANGUAGE - Keunimjaeva, Mekhriban (Журнал иностранных языков и лингвистики, 2025)
In the contemporary era, which is characterized by the prevalence of global connections, the capacity to engage in cross-cultural interactions is becoming an increasingly crucial skill [1; 214]. Loanwords in the Karakalpak language represent a significant and integral phenomenon that reflects the historical, social, and cultural interactions of the Karakalpak people with other nations and languages. Over time, the Karakalpak language has been influenced by neighboring languages—most notably Russian—leading to the incorporation of numerous loanwords into its vocabulary. This process has been ongoing for centuries, typically driven by various aspects of societal life such as trade, politics, education, and international relations.